Pengaruh Terapi Menggambar Untuk Meningkatkan Kepercayaan Diri Anak Usia 3-5 Tahun Di Desa Booi - Fathmy Fitriyani Soulissa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Background: One of the emotional social development of children aged 3-5 years is showing self-confidence. Early childhood often experience things that can reduce their self-confidence because in their growth phase parents and the environment often make yelling sentences, harsh prohibitions, especially curse, will make them present negative emotions and have an impact on feelings of sadness, fear and guilt. Drawing therapy can help children express their feelings. Purpose: This study aims to determine the effect of drawing therapy to increase self-confidence of children aged 3-5 years in the village of booi, saparua district, central maluku district. Methods: This study used an experimental research method with a one-group pre-test post-test design. The population in this study were all 30 children aged 3-5 years in Booi Village. The sampling technique was purposive sample of 20 children. Data collection by means of observation. Bivariate analysis using non-parametric statistical tests with the Wilcoxon test. Results:The Wilcoxon test results (p value 0,000) because the p value <0.05, statistically there is a difference before and after drawing therapy with a median of 0.000 with a minimum-maximum value of 1-5 self-confidence before drawing therapy and a median of 8.50 with minimum-maximum values ​​1-6 after drawing therapy. Conclusion: From the results above, it can be concluded that there is an effect of drawing therapy on increasing self-confidence of children aged 3-5 years in the village of booi, Saparua sub-district, Central Maluku district.